A survey of tasks performed by School Library Media Center personnel in selected private schools in Metro Manila - Buenrostro, Joel S.; Buenrostro, Juan Jr. C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1996)
This study aims to identify the tasks performed by a variety of personnel in exemplary school library media center programs in Metro Manila. The descriptive survey method was used. The subjects were the SLMC professional and support staff of four selected private schools in Metro Manila, namely : Assumption College, Ateneo de Manila University, Claret School and Xavier School. A questionnaire patterned after the task analysis survey instrument developed for the School Library Manpower Project by Research Division of the National Education Association was used to gather data.
The findings of the study revealed that the head of the SLMC performs library and administrative duties in SLMC operations; the SLMC specialist or school librarian performs most of professional responsibilities and media oriented duties; the A-V specialist applies expertise in management of both print and non-print materials and related A-V equipment; the SLMC technician performs the technical services in the SLMC program; and the paid adult clerk/aide performs the routine clerical activities in the SLMC operations. Based on the findings revealed, the study concludes that different SLMC personnel has different performed tasks and duties related to their area of specialization, knowledge, abilities, a d competencies. "
Typescript.
Vita.
Thesis (Bachelor of Library Science)--University of the Philippines Diliman
Keywords: Instructional materials personnel -- Philippines -- Manila Metropolitan Area; Private and school libraries -- Philippines -- Manila Metropolitan Area